1992
DOI: 10.2307/1940022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bird Predation on Grasshopper Densities in an Arizona Grassland

Abstract: In a 4—yr field experiment, we tested the hypotheses that insectivorous birds (1) controlled densities of herbivorous grasshoppers in an ungrazed semiarid grassland in southeastern Arizona, and (2) functioned as keystone predators, by limiting abundances of grasshoppers that otherwise might change vegetation cover and species composition, and/or by mediating the effects of otherwise competitively superior members of the grasshopper assemblage. We measured grasshopper densities and vegetation on 32 464—m2 grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
3
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 40 publications
4
93
3
2
Order By: Relevance
“…Birds are highly mobile and, with over 50% of all species primarily insectivorous, are ideal providers of pest control services (Wenny et al 2011). Birds have been shown to decrease insects in a variety of systems (Bock et al 1992, Mols and Visser 2002, Kellermann et al 2008, Jedlicka et al 2011, Karp et al 2013. Furthermore, studies have shown that birds not only reduce pest populations, but that plants respond with higher levels of productivity (Whelan et al 2008, Mooney et al 2010.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Birds are highly mobile and, with over 50% of all species primarily insectivorous, are ideal providers of pest control services (Wenny et al 2011). Birds have been shown to decrease insects in a variety of systems (Bock et al 1992, Mols and Visser 2002, Kellermann et al 2008, Jedlicka et al 2011, Karp et al 2013. Furthermore, studies have shown that birds not only reduce pest populations, but that plants respond with higher levels of productivity (Whelan et al 2008, Mooney et al 2010.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Grasslands have received a relatively large amount of attention with regard to top-down and bottom-up control (Bock et al 1992;Schmitz 1994Schmitz , 1998Chase 1996Chase , 1998Moran et al 1996;Beckerman et al 1997;Schmitz et al 1997;Moran and Hurd 1998;Ritchie 2000;Schmitz and Suttle 2001;Moran and Scheidler 2002), and these studies have demonstrated that both top-down and bottom-up processes are prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…In terrestrial ecosystems, the indirect effects of firstand second-order predators on plant performance has been studied through field experiments in a number of systems: carnivores through predation on grazing mammals (McLaren and Peterson 1994), spiders (Carter and Rypstra 1995) and mantids (Moran and Hurd 1998) through predation on herbivorous insects, Anolis lizards through predation on Homoptera (Spiller and Schoener 1990;Dial and Roughgarden 1995;Spiller and Schoener 1997), beetle larvae through predation on ants (in an antplant mutualism system; Letourneau and Dyer 1998), and birds through predation on herbivorous insects (Loyn et al 1983;Atlegrim 1990;Bock et al 1992). Assessment of plant performance has primarily been through quantification of leaf damage to the plants as mediated by predation pressure on the herbivores.…”
Section: Introductionmentioning
confidence: 99%